STRUKTUR, KINERJA, DAN KLUSTER INDUSTRI ROKOK KRETEK: INDONESIA, 1996-1999 - Simon Bambang Sumarno; Mudrajad Kuncoro (Journal of Indonesian Economy and Business (JIEB), 2003)
This paper attempts to illuminate the dynamics of Indonesia’s clove cigarette industryusing Structure-Conduct-Performance (SCP) paradigm and industrial cluster approach.We employed concentration ratios (CR4, CR8, and IHH) and performance ratios in SCPanalysis. To identify industrial clusters, we used Geographic Information System (GIS) andsome tools of analysis, mainly size and specialization index. The structure of clove cigarette industry suggested that an oligopoly with high concentration has been found, albeit declined slightly over the period 1996-1999. As far as geographic concentration isconcerned, we found that this industy has clustered overwhelmingly in and around Kudus,Kediri, Surabaya, and Malang.Keywords: oligopolistic industry, concentration ratio, cluster